Nothing natural is shameful: sodomy and science in late medieval Europe - Cadden, Joan (The Middle Ages series, 2013)
Introduction : the natural philosophy of sodomites and their kind -- Moved by nature -- Habit is a kind of nature -- "Just like a woman" : passivity, defect, and insatiability -- "Beyond the boundaries of vice" : moral science and natural philosophy -- What's wrong? : silence, speech, and the Problema of sodomy -- Epilogue -- Appendix. Pietro d'Abano, Expositio problematum Aristotelis, IV.26 : a text -- Notes -- Manuscripts consulted -- Works cited -- Index -- Acknowledgments